PEMBUATAN MESIN PENGADUK ADONAN UNTUK MENINGKATKAN PRODUKSI PADA USAHA KECIL PENJUAL MARTABAK - Widodo, Rahmat Doni; Khumaedi, Muhammad (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
This  devotion  activity  carried  out  with  the  aim  to  help  problems  that  were  be- ing  faced  by  small  business  sellerof  martabak  “Bangka”. Activity  specific target  of  this  de- votion  is  to  generate  the  external  aspects  of  production  such  as:  making  dough  mixer machine of sweet martabak that is rotated with electric motor. The methods used for the imple- mentation of this activity was done in various ways that support each other, namely: coordina- tion, machine building, training of machine operating, accompanying partners during the ac- tivities in progress and evaluating activity results. The result of this devotion activity is dough stirring machine with ¼ PK that time of the stirring becomes five times faster, stirring dough results  become  smoother,  production  increases,  as  well  as  income  and  increasing  its  profits